Mastery goals and foreign language reading enjoyment among Chinese EFL undergraduate learners - Yu, Han Wang; Hasliza Abd Halim (Penerbit Universiti Kebangsaan Malaysia, 2025)
Extensive studies have confirmed that mastery goals can influence learners’ enjoyment in multiple educational contexts, while the enjoyment specific to foreign language reading has never been empirically explored. The study, therefore, aimed to investigate the relationship between mastery goals and foreign language reading enjoyment through a mixed-method research design. The quantitative phase involved 119 EFL undergraduate learners in China completing a self-reported questionnaire. The Pearson correlation analysis confirmed mastery goals can positively and significantly predict the enjoyment of foreign language reading. One hundred eight participants from the quantitative phase agreed to join the qualitative study. One participant was invited to the subsequent semi-structured interview, and the data was analyzed thematically. The qualitative findings reinforced the quantitative results, offering deeper insights into the relationships between mastery goals and foreign language reading enjoyment. Learners’ experiences highlighted that mastery goals for foreign language reading were driven by their interest and the practical utility of the reading materials, which in turn fostered satisfaction and a sense of achievement toward reading and further enhanced their foreign language reading enjoyment.